Dantrolene an unusual option for detrusor overactivity: observations of a patient with cerebral palsy. (November 2015) - Bulchandani, Supriya; Toozs-Hobson, Philip; Kennedy, Angus; Sturman, Steve
Abstract: We report a case of a 49-year-old female with cerebral palsy with spastic tri-plegia and lumbar spondyolisthesis diagnosed to have overactive neurogenic bladder, which improved on treatment with Dantrolene along with antimuscarinics. She was initially treated with antimuscarinics both transdermal and oral simultaneously and later received intravesical OnaBotulinum toxinA. Following lumbar spine fixation for spondylolisthesis, her bowel and bladder function deteriorated and she was commenced on Dantrolene for her spasticity, along with being on Oxybutinin and Mirabegron. This significantly improved her symptoms. Overactive bladder symptoms are a common manifestation in cases of CP. In refractory cases where antimuscarinics and intravesical botulinum toxin therapy have failed, a combination of Dantrolene with antimuscarinics and/or beta 3 receptor agonists may prove to be beneficial. While on therapy, regular monitoring of liver functions is required to promptly diagnose and treat hepatotoxicity.